CLASSIFICATION AND COLLECTION OF SOLID MEDICAL WASTE AT SOME GENERAL PUBLIC HOSPITALS IN VIETNAM IN 2017 (Vietnam Journal of Community Medicine, 2022)
Objectives: To describe the classification and collection of solid medical waste of some generalpublic hospitals in Vietnam in 2017.Research method: A cross-sectional quantitative study was conducted at 200 departments of 40general public hospitals.Results: Indicators of containers of solid medical waste made up from 67,5%, to 95,5%; 54% waspercentage for achieving all indicators, in which national hospitals accounted for 53,3%, provincialhospitals accounted for 67,3%, district hospitals accounted for 47,8%. In terms of classification ofsolid medical waste, it accounted for 72% to 97%; achieving all indicators accounted for 53%, inwhich national hospitals accounted for 46,7%, provincial hospital accounted for 63,3%, districthospitals accounted for 49,6%. Collection of solid medical waste accounted for 68,5% to 93,5%;achieving all indicators accounted for 44%, in which national hospitals were made up 50%, provincialhospitals made up 60%, district hospitals made up 34,8%.Conclusion: Hospitals have not fully complied with regulations of classification and collection ofsolid medical waste.
Keywords: Classification, collection, solid medical waste.